The interference and elimination of nitrite on determination of total urinary protein by Pyrogallol Red–Molybdate method - Shijian Fan; Jiaqing Liu; Yu Wei; Jie Yao; Juan Cheng; Yang Tong; Qiang Zhou; Yuanhong Xu (Practical Laboratory Medicine)
Background: Some urine samples showed negative values of total urinary protein by Pyrogallol red–molybdate (PRM) method. Interestingly, these samples showed notably high levels of nitrite in the urine dipstick test. Methods: A total of 120 urine samples were collected and categorized into four groups (0 - < 100, 100-<500, 500-<1000, ≥1000 mg/L) based on total urinary protein concentration. Various concentrations of nitrite (2, 10, 50, 100, and 200 mg/L) were added to urine samples to investigate potential interference of nitrite in total urinary protein measurement by the PRM method. Additionally, different concentrations of L-ascorbic acid (100, 500, 1000, and 2000 mg/L) were added to urine-nitrite mixtures to explore the possibility of reversing the interference effects. Results: 2 mg/L nitrite had no impact on the test results.10 mg/L nitrite only showed significant effects on the detection results among the groups with 0 - < 100 and 100-<500 mg/L (P < 0.05). 200 mg/L nitrite caused a noticeable decrease in the urinary protein detection results of the four groups (0 - < 100, 100-<500, 500-<1000, ≥1000 mg/L), and the concentrations were reduced to 2.7 %, 26.85 %, 75.22 %, and 89.33 % of their original levels, respectively. 500 mg/L L-ascorbic acid effectively eliminated the interference from 200 mg/L nitrite and almost had no effect on detection. Conclusions: Nitrite had negative effect on the detection of total urinary protein by PRM method and L-ascorbic acid was effective in counteracting the interference caused by nitrite.